(untitled) (Modern Problems of Metallurgy, 2023)
It is proposed to use the PDE Toolbox application of the Matlab mathematical package, which provides the solution of differential equations in partial derivatives by the finite element method for modeling the friction pair of the interaction of the drive drum and the conveyor belt, as a thermal model with distributed parameters, of the belt conveyor as an element of the technological process of transporting ore masses The application contains a graphical interface; means of determining the type of equations and boundary conditions; the order of automatic formation of the grid of finite elements; tools for visualization of the obtained solution and its animation. The obtained results of calculations in the PDE Toolbox Matlab program, which make it possible to obtain the thermal field of the friction pair for the emergency and working modes of operation of the drive drum of the investigated conveyor of the technological chain of cargo flow transportation, which are determined by the initial and boundary conditions and coefficients of the Fourier heat conduction equation.